Computational evaluation of fluid flow influencing geometrical parameters of cyclone separator for Cement Kiln - Mohnish Kumar; Harshad Deshpande; Sameer Bhosale; Himadri Majumder; Ch. Sateesh Kumar; Alemu Workie Kebede; Manish Deshmukh (PLoS ONE, 2026)
Cyclone separators are integral to cement kiln operations, serving as key devices for mitigating air pollution and reducing particulate matter. Computational Fluid Dynamics (CFD) simulations enable visualization of internal flow distribution and provide quantitative insights into separator performance. A numerical CFD model was developed for the cyclone geometry, with the simulation results validated against existing experimental data. This study employs the design of experiments (DoE) technique to optimize design parameters and to examine how distinctive geometric features influence cyclone efficiency. An optimization study utilizing the design of experiments (DoE) technique was conducted to refine the design parameters for enhanced cyclone performance. This study investigated the impact of modifying key geometrical features of a cyclone separator on its performance metrics. The fluid flow performance influencing geometrical parameters considered in this study are the inlet height ratio (I H /D b = 0.25 to 0.75), inlet width ratio (I W /D b = 0.1 to 0.3), particle exit diameter ratio (D e /D b = 0.2 to 0.4), bottom cone length ratio (L c /D b = 1.75 to 2.75), and vortex finder diameter and length ratio (D v /D b and L v /D b = 0.25 to 0.75). Here, the term “ratio” refers to the ratio of the respective dimension to the cyclone barrel diameter (D b ). The optimized design features an inlet height ratio of 0.5, an inlet width ratio of 0.21, a particle exit diameter ratio of 0.26, a bottom cone length of 2.31, and a vortex finder with a 0.5 in diameter and a 0.55 in length. This configuration resulted in a pressure drop of 285 Pa and an efficiency of 96%.